ANALISIS PERSEPSI, SIKAP DAN PERILAKU KONSUMEN TERHADAP PANCAKE DURIAN (STUDI KASUS : PANCAKE DURIAN PRODUKSI CELEBRITY PANCAKE) - Marbun, Desyanti; Priyono, Basuki Sigit; Suryanty, Melli (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2015)
The research was aimed to analyze the perception, attitude and behavior of consumer durian pancakes production Celebrity Pancake. Research method: study area is defined as purposive on the street S.Parman in the city of Bengkulu. Consumer respondents were taken by used accidental sampling. Intended for consumers who purchase the products of durian pancake at Celebrity Pancake. Methods of data analysis used Likert scale, analysis of descriptive, and Fishbein. The result showed, consumer perceptions to attribute durian pancakes had been different result, that is attribute taste, flavour, color, and sachet appear are in good category, while the price is at category less well, The consumer attitudes to durian pancakes which indicated trend to a positive attitude. The consumer behaviour to durian pancakes product indicated behaviors liking. Consumer considers all the important attributes of the durian pancakes product.